Desahuciados medioambientales. Historias de vida - Alena Kárpava; Matías Bedmar-Moreno (Universidad Autónoma del Estado de México, 2015)
This work is part of a larger piece of research focusing on the study of Belarusian immigration in the Province of Granada. The research is based on a qualitative methodolog y of a hermeneutic character. It responds to a biographical-narrative study, using a life history strateg y and semi-structured, biographical and in-depth interviews, as data-collection tools. Its conclusions connect the integration difficulty of this group with the weakness of cultural identity and the links of environmental migration to nuclear industry development. Familiarity with the peculiarities of the Belarusian immigrant group led us to propose the elaboration of a program to strengthen their cultural identity in order to facilitate their process of integration.